2018
DOI: 10.1371/journal.pone.0206058
|View full text |Cite
|
Sign up to set email alerts
|

Newcastle disease vaccine adoption by smallholder households in Tanzania: Identifying determinants and barriers

Abstract: BackgroundFood security is critical to achieving sustainable growth, poverty reduction, and political and economic stability. Livestock have the potential to improve the food security of smallholder households in developing countries, but livestock productivity is constrained by disease. The extent to which households adopt innovations such as vaccines impacts disease control; however, the behavioral and economic drivers underlying household decisions to adopt or forgo vaccination are not well understood. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 18 publications
6
53
0
Order By: Relevance
“…Before commencement of the present study, we obtained an informed consent through the camp agriculture extension officer of the research sites at the time of recruitment of the participants to the study, by reading and interpreting the designed consent form. This is in line with [21], who reported that oral consent has an advantage over written consent as it includes all respondents of any literacy scale. The informed consent spelt out the purpose of the study and any likely benefits and disadvantages which were to be accrued.…”
Section: Ethical Considerationssupporting
confidence: 86%
“…Before commencement of the present study, we obtained an informed consent through the camp agriculture extension officer of the research sites at the time of recruitment of the participants to the study, by reading and interpreting the designed consent form. This is in line with [21], who reported that oral consent has an advantage over written consent as it includes all respondents of any literacy scale. The informed consent spelt out the purpose of the study and any likely benefits and disadvantages which were to be accrued.…”
Section: Ethical Considerationssupporting
confidence: 86%
“…The first section of the survey measured household demographics and socioeconomic status, as well as knowledge, attitudes, and practices with regards to chicken-keeping. The socioeconomic drivers of adoption are described by Campbell et al [10]. The second portion of the survey consisted of a double-bounded contingent valuation activity where respondents within a household were asked if they were willing to pay 2000 Tanzanian shillings (TZS), equivalent to $0.90 USD, to vaccinate ten chickens for ND within the context of a specific, hypothetical scenario.…”
Section: Methodsmentioning
confidence: 99%
“…In a study concurrent to the one described here, Campbell et al identified determinants and barriers to adoption of Newcastle disease (ND) vaccines in Tanzania. Knowing someone who vaccinated and having a larger flock increased the odds of previous vaccination while using traditional medicines to treat or prevent ND decreased the odds of previous vaccination [10]. Notably, income in the previous month was not significantly associated with previous or recent vaccine use [10].…”
Section: Introductionmentioning
confidence: 92%
“…e disease control and prevention strategies largely depend on proper adoption of vaccination programs and good farm management practices like an appropriate institution of biosecurity measures [5,6]. However, vaccination programs and vaccination adoption remains a challenge under backyard production systems in rural areas of developing countries in SSA due to lack of financial resources [4,7]. Moreover, the free movement of birds scavenging for their nutritional needs in backyard chickens halts the institution of biosecurity measures [8].…”
Section: Introductionmentioning
confidence: 99%